Numerical and experimental investigations of three-dimensional container filling with Newtonian viscous fluids - Tome, M. F.; Castelo, A.; Nobrega, J. M.; Carneiro, O. S.; Paulo, G. S. [UNESP]; Pereira, F. T. (Elsevier B.V., 2014)
This work employs numerical and experimental approaches to investigate three-dimensional container filling with Newtonian viscous fluids. For this purpose, a computer code developed for simulating three-dimensional free surface flows has been used. The CFD Freeflow3D code was specifically designed to deal with unsteady three-dimensional flows possessing multiple moving free surfaces. An experimental apparatus that allows the visualization of the various phenomena that can occur during the filling of containers has been constructed and employed. Experiments on container filling were carried out by varying the fluid velocity at the injection nozzle. This paper presents a computational study on container filling with Newtonian viscous fluids and employs the experimental results to validate the software. The experimental observations were compared with the predictions from the Freeflow3D code and good agreement between the two sets of results is observed. Moreover, the code predictions showed that it is capable of capturing the most relevant phenomena observed in the experiments. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Container filling; Jet buckling; Three-dimensional free surface flows; Experimental assessment; Finite differences